Analisis Biaya Tambahan Dalam Hubungannya Dengan Decision Making Ud. Sinar Abadi Singaraja - Ni Kadek Ayu Trisna Dewi; Ni Wayan Novi Budiasni (ARTHA SATYA DHARMA, 2021)
This study aims to determine (1) the separation of semi-variable costs into variable costs and fixed costs for determining the contribution margin in making order decisions at UD. Sinar Abadi Singaraja in 2020 and (2) applying differential costs in making order decisions at UD. Sinar Abadi. Singaraja in 2020. This research is a descriptive study with a quantitative approach. The subject of this research is UD.Sinar Abadi Singaraja and the object of this research is the differential cost in making pressure decisions. The data were collected using the documentation method, then analyzed using the least squares regression method and differential cost analysis. The results showed (1) the separation of semi-variable costs of Rp. 15,475,570 separated into variable costs Rp. 7,509,327.01 and fixed costs of Rp. 7.966.242.98 (2) analysis of differential costs in making order decisions states that, by issuing an additional cost of Rp. 1,353,257.4 for making pia cake skin can cover the variable cost of Rp. 21,344,950 as well as creating a positive contribution margin of Rp. 19,905,050 and providing additional profit for the company amounting to Rp. 18,551,792.6 so that the special orders offered can be accepted.